Development of o-aminobenzamide salt derivatives for improving water solubility and anti-undifferentiated gastric cancer - Li, Shuang; He, Yanli; Li, Xuelin; Xiong, Yongxia; Peng, Yan; Wang, Chengkun; Zhuo, Linsheng; Jiang, Weifan; Lu, Xianzhou; Wang, Zhen (Frontiers in Pharmacology, 2023)
Gastric cancer is one of the cancers with wide incidence, difficult treatment and high mortality in the world, especially in Asia and Africa. In our previous work, a novel o-aminobenzamide analogue F8 was identified as an early preclinical candidate for treatment of undifferentiated gastric cancer (IC50 of 0.26 μM for HGC-27). However, the poor water solubility of compound F8 prevents its further progress in preclinical studies. It is well known that salt formation is considered to be the most feasible method of improving water solubility and optimizing drug-likeness in drug discovery. Here, our continuous efforts have finally confirmed F8·2HCl as the optimal salt form with maintained in vitro antitumor activity, improved water solubility and pharmacokinetic properties. Importantly, the F8·2HCl displayed superior in vivo antitumor efficacy (TGI of 70.1% in 75 mg/kg) in HGC-27 xenograft model. The further immunohistochemical analysis revealed that F8·2HCl exerts a pro-apoptotic effect through the regulation of cell cycle (CDK2 and Ki-67) and apoptosis (Cleaved Caspase3 and E-cadherin)-related proteins. In addition, F8·2HCl showed acceptable safety in the in vivo acute toxicity assay. The preclinical studies of F8·2HCl are under way.